Prognostic significance of body mass index and weight loss in patients with idiopathic pleuroparenchymal fibroelastosis - Kono, Masato; Saito, Takahiko; Tsunoda, Tomo; Ikeda, Shin; Arano, Takahiro; Watanuki , Masayuki; Katsumata, Mineo; Miwa, Hideki; Miki, Yoshihiro; Hashimoto, Dai; Suda, Takafumi; Nakamura, Hidenori (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2024)
Background and aim: Idiopathic pleuroparenchymal fibroelastosis (IPPFE) is a rare form of idiopathic interstitial pneumonias; its physical characteristics include a slender build with platythorax and progressive weight loss. However, the clinical significance of body mass index (BMI) and weight loss remains unclear in patients with IPPFE. Therefore, we aimed to clarify the association between baseline BMI, weight loss after diagnosis, and the prognosis of patients with IPPFE. Methods: This retrospective study included 71 patients diagnosed with IPPFE at our institution between 2005–2021. BMI at diagnosis was classified into three: underweight (